The New Public Management paradigm as a further interaction of the public and private sectors - V. Nelipa, Dmytro (2020)
The purpose of this study is to determine the impact of the development of the paradigm of the new public management on improving the efficiency of the public administration system; the need to use the basic principles of theory in the practice of public administration; the state's opportunities to benefit from strengthening cooperation between the public and private sectors.